Interactions of Surfactant Proteins A and D with Saccharomyces cerevisiae and Aspergillus fumigatus - Allen, Martin J. (American Society for Microbiology, 2001)
Surfactant proteins A (SP-A) and D (SP-D) are members of the collectin family of calcium-dependent lectins and are important pulmonary host defense molecules. Human SP-A and SP-D and rat SP-D bind to Aspergillus fumigatus conidia, but the ligand remains unidentified. To identify a fungal ligand for SP-A and/or SP-D, we examined the interactions of the proteins with Saccharomyces cerevisiae. SP-D but not SP-A bound yeast cells, and EDTA inhibited the binding. SP-D also aggregated yeast cells and isolated yeast cell walls. Treating yeast cells to remove cell wall mannoprotein did not reduce SP-D binding, and SP-D failed to aggregate chitin. However, SP-D aggregated yeast glucan before and after treatment with a β(1→3)-glucanase, suggesting a specific interaction between the collectin and β(1→6)-glucan. In support of this idea, SP-D-induced yeast aggregation was strongly inhibited by pustulan [a β(1→6)-linked glucose homopolymer] but was not inhibited by laminarin [a β(1→3)-linked glucose homopolymer]. Additionally, pustulan but not laminarin strongly inhibited SP-D binding to A. fumigatus. The pustulan concentration for 50% inhibition of SP-D binding to A. fumigatus is 1.0 ± 0.3 μM glucose equivalents. Finally, SP-D showed reduced binding to the β(1→6)-glucan-deficient kre6 yeast mutant. Taken together, these observations demonstrate that β(1→6)-glucan is an important fungal ligand for SP-D and that glycosidic bond patterns alone can determine if an extended carbohydrate polymer is recognized by SP-D.